The effect of project funding on innovative performance: An agent-based simulation model - Kristina Bogner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2015)
Analyzing the effect of Direct Project Funding (DPF) on innovative performance of economic agents is a major challenge for innovation economists and policy makers who must give valid policy recommendations and decide on the allocation of financial resources. An approach that becomes more and more important is the use of agent-based modeling in analyzing innovative performance of market players. In this paper, an agentbased percolation model is used to investigate the effects of project funding on innovative performance in terms of the maximum technological frontier that can be reached as well as in terms of the number of innovations generated by firms. The model results show that firms which participate in subsidized projects outperform firms that do not participate in subsidized projects, especially in increasingly complex technological fields. However, the worse performance of firms that do not participate in subsidized projects can be offset by an increase in the firms' financial resources. Hence, the model indicates, the effect of project funding is a purely financial one and might even have negative effects on innovative performance. This is the case if, for instance, a high number of funded research projects disturbs firms' paths through the technology space. Following the results of the model, project funding is most effective and important in increasingly complex technology spaces and less effective and important in less complex technology spaces. Moreover, the model results show, other financial resources as venture capital can substitute for direct project funding.
urn:nbn:de:bsz:100-opus-11537
Keywords: 330; project funding; innovation; technology space; agent-based simulation